2020
DOI: 10.1021/acs.iecr.0c00430
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Contact Angles and Surface Morphology of 3D-Printed Materials

Abstract: In the field of thermal separation technology, additive manufacturing has become increasingly important. 3D-printed components are often characterized by computational fluid dynamics simulations. Therefore, the knowledge of contact angles and surface properties are crucial. Materials used for 3D-printed components have so far not been characterized with sufficient precision, which resulted in limited awareness about contact angles. Within this work, surface characterizations of printable materials consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
16
1
Order By: Relevance
“…There are relatively few publications regarding the wettability of additively manufactured materials. Depending on the production process as well as on the chemical composition, specifically the effect of additives, materials can differ in their surface morphology and consequently in their CAs [ 58 ]. The influence of lignin on the average water contact angles of printed composites is displayed in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…There are relatively few publications regarding the wettability of additively manufactured materials. Depending on the production process as well as on the chemical composition, specifically the effect of additives, materials can differ in their surface morphology and consequently in their CAs [ 58 ]. The influence of lignin on the average water contact angles of printed composites is displayed in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The glass@epoxy durability can be drastically improved when immobilized with nanoparticles. The focus of the current research was to prepare a transparent glass@epoxy with a smooth surface. Thus, tensile and scratch tests were conducted to assess the glass@epoxy mechanical characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle was analyzed using OCA 15 EC (Dataphysics, Stuttgart, Germany). 41 2.5.3. Mechanical Properties.…”
Section: Electrospinning and Silanizationmentioning
confidence: 99%
“…The investigation of the properties of 3D printed materials and their influence on the performance-relevant physical phenomena is also a research topic of the Thermal Process Engineering group at the Ulm University. 32 Depending on the exact 3D printing material specification, it has been observed that residuals of the powder can accumulate in the reboiler during column operation. For this reason, it is advisable to infiltrate the 3D printed column components.…”
Section: Additively Manufactured Componentsmentioning
confidence: 99%
“…In principle, it is not a problem to include column components made of other materials than polyamide, if desired. The investigation of the properties of 3D printed materials and their influence on the performance‐relevant physical phenomena is also a research topic of the Thermal Process Engineering group at the Ulm University 32 . Depending on the exact 3D printing material specification, it has been observed that residuals of the powder can accumulate in the reboiler during column operation.…”
Section: Distillation Test Rigmentioning
confidence: 99%